IMPLEMENTASI METODE POINT UNTUK MENINGKATKAN MOTIVASI BELAJAR MAHASISWA SEMESTER II PROGRAM STUDI PGSD FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS WIDYA GAMA MAHAKAM SAMARINDA, TAHUN AKADEMIK 2017-2018 - Gamar Al Haddar (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study aims to know the implementation of point method in improving students' motivation in the second semester in the subject of sociology and anthropology seen from the implementation process on lectures for one semester.This research is descriptive qualitative research. Instrument in this study is the researcher himself. The data collection techniques used include (1) participant observation (2) interview and (3) documentationThe results showed that the implementation of point method is very effective to improve student's learning motivation. Implementation This method is very appropriate to be applied in social subjects such as sociology and anthropology. In this subject many problem issues are suitable for discussion. The Point Method make students active to ask questions, criticize and advise so students can continue to collect points. The improvement of learning motivation with point point implementation is evidenced by the following points: (1) Students look diligent in doing the tasks given by the lecturers (2) Students study the material before the learning begins (3) Students are broad-minded in receiving criticism. (4) Students are enthusiastic in lectures and (5) Independence and confidence in the argument increases. Keywords: Point Method & Motivation learning